1996
DOI: 10.1007/bf02262741
|View full text |Cite
|
Sign up to set email alerts
|

Critical psychology and the problem of mental health

Abstract: This paper reviews psychological treatment and mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Johnson (1991) found that female officers scored relatively high on exhaustion, whereas males scored relatively high on mental distance, while Kop, Euwema, and Schaufeli (1999) found no difference between male and female police officers. Edwards (1989) and Nell (1994) perceived lower levels of psychological well-being among Black people. Hobfoll and Lilly (1993) found that resistance resources were lower in Black communities.…”
Section: Work-related Well-being and Background Variablesmentioning
confidence: 95%
“…Johnson (1991) found that female officers scored relatively high on exhaustion, whereas males scored relatively high on mental distance, while Kop, Euwema, and Schaufeli (1999) found no difference between male and female police officers. Edwards (1989) and Nell (1994) perceived lower levels of psychological well-being among Black people. Hobfoll and Lilly (1993) found that resistance resources were lower in Black communities.…”
Section: Work-related Well-being and Background Variablesmentioning
confidence: 95%
“…Further, she has found that the bureaucratic power relations extant in society and pervading the health system are replicated in the patient-nurse relationship. The consequent victim-blaming, paternalistic and authoritarian climate traps patients in a role of passivity, disempowerment and socialises them in the medical discourse of subservient patient (Nell, 1994;Seedat & Nell, 1992). Lazarus (1988) also cautioned that the medicalisation of pathology and deficits is antithetical to an empowerment and competency building approach in service delivery.…”
Section: The Context For Mental Health In South Africamentioning
confidence: 97%
“…Drawing on the lessons learnt from her engagements in these commissions, Lazarus (2001) argued that in young democracies like South Africa, community psychologists can make meaningful contributions toward informing and monitoring new social policy developments and debates in social policy. Lazarus (2001) suggests that community psychologists can use their privileged positions to ensure that social policy development remains people-centered without compromising their critical and reflexive roles (Lazarus, 2001;Nell, 1996).…”
Section: Transformation Democracy and Community Psychologymentioning
confidence: 99%